Assessment of knowledge, attitude and practice towards prevention of COVID-19 among undergraduate medical college students - Shrestha, Marina Vaidya; Manandhar, Naresh; Jyoti, Sabita; Chaudhary, Rupesh; Chaulagain, Rajkumar; Chhetri, Komal; Dahal, Nischal; Dhakal, Monalisha; Magar, Neeraj Gharti; Ghimire, Samir (Journal of Chitwan Medical College, 2021)
COVID-19 pandemic is a public health burden and threat all around the world. Good Knowledge, Attitude and Practice towards prevention can break the chain of transmission. The study aimed to assess the knowledge, attitude and practice towards prevention of COVID-19. Methods: This was a cross sectional study conducted during 5th to 28th of October 2020 among undergraduate Medical College students. An online questionnaire was developed using Google Forms. The mean knowledge, attitude, and practice of the participants were assessed, and the scores were calculated. T-test and ANOVA were used for statistical analysis. Results: Out of the total participants (n=274), 48.16 % were male and 51.5% were female. The mean age of the participants was 20.92±1.62 years. Among the total 69.3% had good knowledge, 67.5% had positive attitude and 73.4% had good practice towards prevention of COVID-19. In addition, demographic variable sex had a significant impact on practice scores. Male participants had higher practice scores. (P<0.05). Conclusions: Undergraduate medical college students had good knowledge, positive attitude and good practices. Males and females had significantly different practices.